PENGARUH MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN SELAMA BELAJAR DARI RUMAH DI PAUD KOTA SERANG - BANTEN - Rosmawati Rosmawati; Siti Khosiah; Fahmi Fahmi (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2022)
The Effect Of Animated Video Learning Media On The Listening Skills Ability Of Children Aged 5-6 Years While Studying From Home In PAUD, Serang - Banten. Listening skills is a child's ability to process the delivery of information orally.  Therefore, listening skills is a child's ability needs to be optimized from an early age.  The use of the right learning media has a great influence on optimizing listening skills, especially since learning activities have been held from home due to COVID-19.  In fact, there are still many teachers who have not been able to determine which learning media is a place to support learning activities from home.  This will have an impact on the child's Listening skills ability to be not optimal according to his age.  This study aims to determine the effect of animated video learning media on the listening skills ability of children aged 5-6 years while studying from home in PAUD Serang-Banten city.  The method used in this research is survey research by distributing questionnaires to parents and teachers.  Hypothesis testing in this study used a simple linear regression test because the data were normally distributed.  The results showed that the probability value was 0.000 <0.05 so that H1 was accepted, that is, there was a significant effect of the use of animated video learning media on the listening skills ability of children aged 5-6 years years while studying from home.